PENGUATAN PENDIDIKAN KARAKTER DALAM PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM DI MI ALKHAIRAAT POMBEWE KACAMATAN SIGI BIROMARU KABUPATEN SIGI - Rahmah, Hikmatul; Takunas, Rusli; Hamzah, Erni Irmayanti (Citra Media Publishing, 2024)
This study also aims to explain the form of strengthening character education in learning Islamic cultural history and explain the development of students' character education through learning Islamic cultural history at MI Alkhairaat Pombewe. This research uses a qualitative research approach. The research was conducted at MI Alkhairaat Pombewe, Sigi Biromaru District. Data collection techniques used in this research are observation, interview, and documentation. While the data analysis techniques that the authors use are data reduction, data presentation and data verification. Based on the results of this study indicate that the form of strengthening character education in learning the history of Islamic culture in MI Alkhairaat Pombewe that the implementation of strengthening character education in learning the history of Islamic culture in MI Alkhairaat Pombewe in class III has been implemented by teachers and has instilled character values to students. The form of strengthening character education is that the teacher has implemented religious values, honesty values, tolerance values, discipline values, curiosity, and creativity. The development of students' character education through learning Islamic cultural history at MI Alkhairaat Pombewe is the implementation of character education activities at school has fulfilled the objectives of the planned activities. It has been determined that there is a positive impact obtained, especially class III students at MI Al-Khairaat Pombewe. With this character education program, the school has become more comfortable, clean, violations of school rules have decreased. And from this evaluation it is said that the implementation of the character education program has taken place and succeeded well. The implication of this research is that the competence of SKI teachers must continue to be improved through activities within the school either through peer tutors or bringing in outside sources. So that character education will be more quickly socialized and implemented in all subjects.